Cytotoxicity of hyaluronic acid coated chitosan nanoparticles containing nitric oxide donor against cancer cell lines. (October 2019) - Pelegrino, M T; Baldi, C; Souza, A C S; Seabra, A B
Abstract: The incidence and mortality rates of all types of cancer have a global burden. The lack of specificity of chemotherapy is one of the major problems in cancer treatment and it is related with moderate to severe adverse effects. CD44 is a protein overexpressed in certain types of cancer cells and can be used as an anchor of attachment for nanoparticles decorated with hyaluronic acid (HA). HA is a natural polymer with high affinity for CD44 receptors. In this work, chitosan nanoparticles (CS NPs) were coated with HA to delivery nitric oxide (NO) donor to cancer cells. NO is a small molecule involved in several physiological processes and it has cytotoxicity against cancer cells. HA-coated and uncoated NO-releasing CS NPs were synthesized and characterized by different techniques. Uncoated and HA-coated NO-releasing CS NPs have hydrodynamic diameters of 142.80 ± 2.22 nm and 170.80 ± 0.14 nm, respectively, polydispersity index of 0.282 ± 0.010 and 0.37 ± 0.04, respectively, and a zeta potential values of + 25.20 ± 0.85 mV and + 15.60 ± 0.15 mV, respectively. As expected, the presence of HA layer on the surface of NO-releasing CS NPs increased hydrodynamic size ca . 20%. The encapsulation efficiency of the NO donor into CS NPs was found to be higher than 90%. The kinetic of NO release from uncoated and HA-coated CS NPs has two distinct phases, an initial burst followed by the establishment of a plateau, with a maximum of NO released at 40 mmol·L −1 . At this concentration, NO is expected to have cytotoxic effects. The cytotoxicity of uncoated and HA-coated NO releasing CS NPs showed a concentration-dependent toxicity against human prostatic carcinoma (PC-3) and human uterine cervix carcinoma (HeLa) cell lines. Taken all together, uncoated and HA-coated NO-releasing CS NPs might find important biomedical applications, including cancer in treatment.